PM2.5 constituents and onset of gestational diabetes mellitus: Identifying susceptible exposure windows. (15th December 2022) - Zheng, Yi; Bian, Jiang; Hart, Jaime; Laden, Francine; Wen, Tony Soo-Tung; Zhao, Jinying; Qin, Huaizhen; Hu, Hui
Abstract: Fine particulate matter (PM2.5 ) has been linked to gestational diabetes mellitus (GDM). However, PM2.5 is a complex mixture with large spatiotemporal heterogeneities, and women with early-onset GDM (i.e., diagnosed before 24th gestation week) have distinct maternal characteristics and a higher risk of worse health outcomes compared with those with late-onset GDM (i.e., diagnosed in or after 24th gestation week). We aimed to examine differential impacts of PM2.5 and its constituents on early-vs. late-onset GDM, and to identify corresponding susceptible exposure windows. We leveraged statewide linked electronic health records and birth records data in Florida in 2012–2017. Exposures to PM2.5 and its constituents (i.e., sulfate [SO4 2− ], ammonium [NH4 + ], nitrate [NO3 − ], organic matter [OM], black carbon [BC], mineral dust [DUST], and sea-salt [SS]) were spatiotemporally linked to pregnant women based on their residential histories. Cox proportional hazards models and multinomial logistic regression were used to examine the associations of PM2.5 and its constituents with GDM and its onsets. Distributed non-linear lag models were implemented to identify susceptible exposure windows. Exposures to PM2.5, SO4 2−, NH4 +, and BC were statistically significantly associated with higher hazards of GDM. Exposures to PM2.5 during weeks 1–12 of gestation were positively associated with GDM. Associations of early-onset GDM with PM2.5 in the 1st and 2nd trimesters, SO4 2− in the 1st and 2nd trimesters, and NO3 − in the preconception and 1st trimester were considerably stronger than observations for late-onset GDM. Our findings suggest there are differential associations of PM2.5 and its constituents with early-vs. late-onset GDM, with different susceptible exposure windows. This study helps better understand the impacts of air pollution on GDM accounting for its physiological heterogeneity. Graphical abstract: Image 1 Highlights: Associations of PM2.5 components with GDM onset were examined. Differential associations with early-vs. late-onset GDM were found. Susceptible exposure windows are different for early-vs. late-onset GDM.